2019
DOI: 10.1186/s40494-019-0283-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solvent on PARALOID® B72 and B44 acrylic resins used as adhesives in conservation

Abstract: Paraloid ® is one of the most frequently used acrylic polymers, employed mainly for its adhesive and consolidating properties in the conservation of a wide range of materials. Appreciated for its reversibility, mechanical characteristics and ease of use, application of the polymer requires it to be simply dissolved in a solvent. Nevertheless, the chemical nature of the relevant solvent must be regarded as an essential parameter, due to its influence on the physico-chemical characteristics of the resulting adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…For comparison, 10 mg/mL Paraloid B72 (previously, Acryloid B72) in ethanol or toluene was similarly applied on wood, paper, and fabric. This copolymer of ethyl methacrylate and methyl acrylate is traditionally used as a transparent and stable varnish, adhesive, and finishing material suitable for metals, stone, glass, ceramics, wood, paper, paintings and textile conservation . Although in most cases Paraloid B72 is not conventionally used as a permanent coating for pliable artifacts such as flexible papers, synthetic acrylic copolymers can be occasionally applied to consolidate and protect this type of substrate …”
Section: Methodsmentioning
confidence: 99%
“…For comparison, 10 mg/mL Paraloid B72 (previously, Acryloid B72) in ethanol or toluene was similarly applied on wood, paper, and fabric. This copolymer of ethyl methacrylate and methyl acrylate is traditionally used as a transparent and stable varnish, adhesive, and finishing material suitable for metals, stone, glass, ceramics, wood, paper, paintings and textile conservation . Although in most cases Paraloid B72 is not conventionally used as a permanent coating for pliable artifacts such as flexible papers, synthetic acrylic copolymers can be occasionally applied to consolidate and protect this type of substrate …”
Section: Methodsmentioning
confidence: 99%
“…Compared to other solvents for the preparation of acrylic resins-i.e., Paraloid ® B72 and B44 -, ethyl lactate is not sufficiently volatile for this purpose [105]. The fact that it remains partially trapped inside the adhesive itself has posed concerns on the potential consequences on the mechanical properties of the film and the treated artifact.…”
Section: Ethyl Lactatementioning
confidence: 99%
“…The topic of troposphere ozone formation caused by road marking paints has been reported by the brief note of Scorgie 21 and Burghardt 22,23 . Vinçotte et al 24 reported the effect of solvent on acrylic resins used as adhesives of road marking. Zhen et al 25 studied the synthesis and properties of hydroxy acrylic resin with high solid content.…”
Section: Introductionmentioning
confidence: 99%